Collision-Free Distributed Adaptive Resilient Formation Control for Underactuated USVs Subject to Intermittent Actuator Faults and Denial-of-Service Attacks - Wu, Xiangjun; Zong, Guangdeng; Wang, Huanqing; Niu, Ben; Zhao, Xudong (IEEE transactions on vehicular technology, 2025)
This paper investigates a collision-free distributed fuzzy adaptive resilient formation control scheme for underactuated unmanned surface vehicles (USVs) with unknown nonlinear dynamics under intermittent actuator faults and denial-of-service (DoS) attacks, where all network communication links between USVs are interrupted in attack active intervals simultaneously. First, fuzzy logic systems are used to approximate unknown nonlinear dynamics. Then, using an artificial potential field method, potential function with continuous partial derivative is designed and integrated into a resilient distributed formation estimator. A novel collision avoidance resilient distributed formation estimator is proposed to ensure the existence of the first-order derivative of estimator states and achieve collision-free between USVs. Meanwhile, a simple prescribed performance function is designed to ensure transient and steady-state formation performances of underactuated USVs. Subsequently, combining dynamic surface control and adaptive technology, an adaptive fault-tolerant control algorithm is proposed to deal with intermittent actuator faults. It is shown that the designed controller can steer formation tracking errors into a residual set of predefined accuracy within a preassigned settling time while avoiding collision between USVs, and ensure all signals in the closed-loop system are semi-globally uniformly ultimately bounded. Finally, a simulation example confirms the effectiveness of the presented theory and approach.